Strategi Pembelajaran Pendidikan Agama Islam Bagi Generasi Millenial di Era Revolusi Industri 4.0 (Studi Multisitus Di SMA Surya Buana Kota Malang Dan SMA Islam Nusantara Kota Malang) - teguh, angga (Proceeding of International Conference on Islamic Education (ICIED); Vol 4 No 1 (2019): Proceeding of International Conference on Islamic Education (ICIED), 2020)
Entering the era of the industrial revolution 4.0, teachers of Islamic religious education face major challenges. Millennial generation and global labor market competition are two major challenges of Islamic religious education teachers in carrying out their duties. This research aims to reveal and explain the strategies of Islamic religious education teachers in improving the life skills of millennials in the digital revolution era 4.0. This study uses a qualitative approach with a multi-case study design. The results showed a change in behavior in the millennial generation, especially in the aspects of ubudiyah, habblumminallah habblumminannas, an increase in soft and hard skills in students as well as a positive impact on the lifestyle of a Muslim personality.